2015
DOI: 10.17675/2305-6894-2015-4-1-057-074
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced corrosion inhibition of mild steel in CO2-saturated solutions containing some novel green surfactants based on cottonseed oil

Abstract: Some novel green surfactants based on cottonseed oil were synthesized and tested as inhibitors for the corrosion of mild steel in CO 2 -saturated 1% NaCl solution by potentiodynamic polarization and linear polarization resistance corrosion rate measurements at 50°C. Their critical micelle concentrations at equilibrium in water at 25°C were also determined. Inhibition efficiency increased with increase in the concentration of the studied surfactants, reached the maximum (99.34%) at 100 ppm. The Tafel polarizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…The vast majority of these studies investigated extracts obtained from various parts of plants, including roots, [31a] bark, [101] leaves, [30c,31b,78–79,90,112‐113] seeds, [30d,79e] and fruits (including the peel of certain fruits) [30c,71c,79b,88a–c,143] as CIs for steel in a CO 2 environment (Table S9 in Supplementary Material). It was also reported that natural products are used to either synthesize [37,104–105,107c,118b,119‐120,131a‐c,e,144] or modify other compounds [128c,f,131d] that have been tested as CIs in a CO 2 environment (Table S10 in Supplementary Material). In addition, the corrosion inhibition effectiveness of extracellular polymeric substances extracted from waste activated sludge [77] and berberine extracted from Coptis chinensis [67c] was evaluated for CS immersed in CO 2 ‐saturated 3.64 wt.% NaCl solution and for L360 steel immersed in CO 2 ‐saturated 3.5 wt.% NaCl solution, respectively.…”
Section: Corrosion Inhibition Of Steel In a Co2 Environmentmentioning
confidence: 99%
“…The vast majority of these studies investigated extracts obtained from various parts of plants, including roots, [31a] bark, [101] leaves, [30c,31b,78–79,90,112‐113] seeds, [30d,79e] and fruits (including the peel of certain fruits) [30c,71c,79b,88a–c,143] as CIs for steel in a CO 2 environment (Table S9 in Supplementary Material). It was also reported that natural products are used to either synthesize [37,104–105,107c,118b,119‐120,131a‐c,e,144] or modify other compounds [128c,f,131d] that have been tested as CIs in a CO 2 environment (Table S10 in Supplementary Material). In addition, the corrosion inhibition effectiveness of extracellular polymeric substances extracted from waste activated sludge [77] and berberine extracted from Coptis chinensis [67c] was evaluated for CS immersed in CO 2 ‐saturated 3.64 wt.% NaCl solution and for L360 steel immersed in CO 2 ‐saturated 3.5 wt.% NaCl solution, respectively.…”
Section: Corrosion Inhibition Of Steel In a Co2 Environmentmentioning
confidence: 99%
“…Generally the values of ΔG ads up to -20 KJ/mol signify physisorption, which is consistent with electrostatic interaction between charged molecules and a charged metal. The values around -40 KJ/mol or higher involve charge sharing or transfer from the inhibitor molecules to the metal surface to form a co-ordinate type of bond [38][39][40][41]. In this study, the calculated values of ΔG ads are around -30 KJ/mol, indicating that the adsorption of mechanism of PFLE on mild steel in 1 M hydrochloric acid solution at the studied temperatures is both physisorption and chemisorption [41][42][43].…”
Section: Adsorption Isothermmentioning
confidence: 83%
“…It has been found that values of ΔH ads are negative, suggesting that the adsorption of inhibitor is an exothermic process, which means lower inhibition efficiency at high temperature. This indicated the gradual desorption of inhibitors from the surface of mild steel [40]. All values of 0 ads S  are negative.…”
Section: Adsorption Isothermmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been acknowledged that CO 2 corrosion is one of major corrosion types resulting in oil well failure [1]. Due to the complexity of environment in oil well, CO 2 corrosion is dependent on various environmental conditions like temperature, CO 2 partial pressure, flow conditions and protective corrosion scales [2][3][4][5][6][7]. Corrosion inhibitors are the most effective and flexible mean of corrosion control in oil and gas production systems, but the selection and application of inhibitors are actually complicated because of the variable corrosive environments in these systems [8].…”
Section: Introductionmentioning
confidence: 99%